The trends of islamic banking: opportunities and challenges for the european banking sector - Martins, Francisco Serrão Santos Moreira (2015)
This project analyzes the growth and importance of Islamic Finance and Banking, and the existing opportunities for the European conventional banking system. Two similar, but nonetheless different concepts. Both Islamic and European banking systems operate under the same globalized world and have the same capacity to provide products and services to clients and investors, however with two distinct business models: The first operates under the Islamic law (Sharia) prohibiting interest-based services in order to develop a better sustainable world and clean business types of services; while the second operates in a basis of interest, unbalancing sustainability. The present paper analyzes those differences by defining what Islamic banking is, its growth in the world and involvement in Europe, as well as the opportunities presented by it after realizing the different and better resistance during the global financial crisis in 2007-2008. As to better understand the subject, the project analyzes the financial institution BNP Paribas, its strategies and how it recognized the importance of this type of products and got involved into it especially in the Middle East but also in Europe, Asia and Africa, being present in many projects involving billions in wealth. A conclusion is then exposed explaining how Islamic banking is clearly a growing market that should be explored as it contains many more present opportunities compared to threats.